DOP27 Humoral immune response after SARS-CoV-2 vaccination in patients with immune-mediated inflammatory diseases treated with immunosuppressive therapy - a Target to B! study. (21st January 2022) - Volkers, A; Wieske, L; van Dam, K; Steenhuis, M; Stalman, E; Kummer, L; van Kempen, Z; Killestein, J; Tas, S; Boekel, L; Wolbink, G; Takkenberg, B; et al.
Abstract: Background: The aim of this study was to investigate the effect of various immunosuppressants on the humoral immune responses after vaccination against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods: The Target to B! SARS-CoV-2 study is a multicentre study, taking place in 7 Dutch academic hospitals. Patients with the following IMIDs were recruited: Crohn's disease (CD), ulcerative colitis (UC), auto-immune hepatitis, rheumatic (e.g. rheumatoid arthritis), neurological (e.g. multiple sclerosis) and dermatological IMIDs (e.g. atopic dermatitis). Patients were recruited based on immunosuppressants (table 1) and previous SARS-CoV-2 infection. The control group consisted of healthy subjects and IMID patients without immunosuppressants. SARS-CoV-2 receptor binding domain (RBD) antibodies were measured 28 days after completed SARS-CoV-2 vaccination. Seroconversion was defined as anti-RBD IgG >4 AU/mL. In this abstract, we focus on therapies relevant for inflammatory bowel diseases (IBD) and present results for these treatments from patients with IBD, but also other IMIDs. Results: Numbers of recruited patients with each immunosuppressant are shown in table 1. Amongst these patients, 312 patients had CD and 176 UC, the rest was diagnosed with another IMID. Seroconversion was reduced in patients receiving sphingosine 1-phosphate (S1P) modulators (all multiple sclerosis patients) while seroconversion was similar to controls in the other treatment groups. However, use of Anti-tumour necrosis factor (TNF), methotrexate, janus kinase (JAK) inhibitor monotherapy and all combination therapies (except for corticosteroids combined with other immunosuppressants) were associated with reduced Sars-CoV-2 antibody titres. Patients with a previous SARS-CoV-2 infection had higher median antibody titres after second vaccination than those without a previous SARS-CoV-2 infection. The type of IMID did not affect seroconversion rates. Conclusion: No immunosuppressant, registered for IBD, reduced the rates of seroconversion after vaccination against SARS-CoV-2. Some immunosuppressants were associated with lower antibody titres. However, the clinical relevance of lower antibody titres remains unknown. S1P modulators, had a clear negative impact on the humoral response against SARS-CoV-2 after vaccination. This might be relevant in the future as this therapy is currently being approved for UC. Disease aetiology did not impair immunity against SARS-CoV-2 immunity after vaccination. Disclaimer: Absolute numbers of antibody titres and rates of seroconversion will be reported at the conference and are not reported in this abstract as this might negatively impact the current submission process.